The Economics of Third-Party Litigation Funding - Doriat-Duban, Myriam; Bourreau-Dubois, Cécile (Studia Oeconomica Posnaniensia, 2026)
Third-Party litigation Funding is growing in many countries, regardless of their legal tradition. Encouraged by a better access to justice this method of fi nan- cing, based on the profi t rather than on the will to enforce the law, could have major consequences on the functioning of justice. Th e economic analysis of law that deals with the impact of the law and legal systems on dispute resolution is a new fi eld of study. Th e objective of this article is to present a synthesis of very recent works on the economics of confl ict on this subject and to show that behind the satisfaction of private interests, the development of this type of fi nancing generates external eff ects both positive and negative, with undetermined consequences in terms of social welfare.